2012
DOI: 10.4236/aim.2012.23045
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Micro-Encapsulated Probiotic <i>Lactobacillus acidophilus</i> R0052 on the Characteristics of Plain Yogurt

Abstract: Micro-encapsulation is a method of providing probiotic living cells with a physical barrier against adverse environmental conditions. Lactobacillus acidophilus is one of the most effective forms of probiotic bacteria and is commercially available as pure culture and encapsulated form. It is not clear whether the use of micro-encapsulated L. acidophilus will result in yogurt of a better quality compared to non micro-encapsulated L. acidophilus. The objective was to determine the influence of micro-encapsulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…Samples including the probiotic organisms were found to have significantly increased the syneresis as compared to the control ( P < 0.05). The syneresis of jellies in groups A and B was approximately the same but far lower than that of group C. Akin to our results, Noland and Aryana () reported that there was no difference between the mean syneresis of microencapsulated and nonmicroencapsulated L. acidophilus in yogurts. The encapsulation with alginate reduced the degree of syneresis up to 24.85% on the second day of storage at 7C.…”
Section: Resultssupporting
confidence: 79%
“…Samples including the probiotic organisms were found to have significantly increased the syneresis as compared to the control ( P < 0.05). The syneresis of jellies in groups A and B was approximately the same but far lower than that of group C. Akin to our results, Noland and Aryana () reported that there was no difference between the mean syneresis of microencapsulated and nonmicroencapsulated L. acidophilus in yogurts. The encapsulation with alginate reduced the degree of syneresis up to 24.85% on the second day of storage at 7C.…”
Section: Resultssupporting
confidence: 79%
“…Before using the pH meter, it was calibrated using reference standard buffer pH 7 and pH 10. Fermented radish kimchi sample was added with 2 ml of autoclaved deionized water and stirred well before pH measurement [ 13 ].…”
Section: Experimental Studymentioning
confidence: 99%
“…There is a demand by the consumer for probiotics due to their health benefits. Probiotics are defined as “live microorganisms which when administered in adequate amounts confer a health benefit on the host” (Hill et al., 2014), which can confer health benefits through digestion, mostly within the intestinal microbiota (Mitropoulou, Nedovic, Goyal, & Kourkoutas, 2013; Noland & Aryana, 2012). Using probiotics as a beneficial food ingredient can dynamically improve the health and wellness of functional foods and appeal among consumers (Banerjee & Dhar, 2019; Kandasamy et al., 2018; Saxelin, 2008).…”
Section: Introductionmentioning
confidence: 99%